(untitled) (Tanzania Medical Journal, 2009)
A 16-year-old boy was admitted with fever, headache, and tender, fluctuant scalp swellings. A lumbar puncture was consistent with meningitis. Aspiration of the mass yielded purulent fluid and cultures yielded Staphylococcus aureus. Treatment with ceftriaxone and gentamicin was initiated. Unfortunately, the patient died before further intervention could be performed. Postmortem exam revealed multiple scalp abscesses, frontal bone osteomyelitis with coronal suture widening, epidural and subdural empyemas, and leptomeningeal inflammation. This presentation is consistent with avariation of Pott’s Puffy Tumor.Key words: Pott’s Puffy Tumor, Staphylococcus aureus, scalp abscess, subdural empyema